From desk to bench: an impossible drill. Contribution of ethnographic research to the debate on the political formation of children and adolescents - Batallán, Graciela; Rodríguez Bustamante, Lucía; Ritta, Loreley (Revista de Antropología Social, 2021)
This research essay delves into the enigmatic relationship between minors and politics. Although the promulgation of the International Convention on the Rights of the Child represented a consensus on the importance and right to participation of these subjects in this field of social life, the research documents that citizen training aimed at this age group manifests tensions that are based on the social delegitimization of their ability to participate in the political field. For the study of this problem, the development of a political education program of the City of Buenos Aires aimed at students of primary and secondary schools is taken as emerging. The research unfolds on the axis of "participation", both the changes of orientation of this public policy, as well as the protagonism of children and adolescents in a role play in which they express proposals, claims and debates, ethnographically documented during the period 2004 -2014.